2010
DOI: 10.3109/09537101003602483
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells from bone marrow show a stronger stimulating effect on megakaryocyte progenitor expansion than those from non-hematopoietic tissues

Abstract: In order to evaluate whether mesenchymal stem cells (MSCs) from non-hematopoietic tissues are able to regulate megakaryocytopoiesis, we identified human MSCs from adult bone marrow (ABM), fetal pancreas (FPan) and umbilical cord (UC), and their abilities to support megakaryocyte (MK) differentiation from CD34(+) hematopoietic progenitor cells (HPCs) were comparatively studied. First, MSCs were isolated from ABM, FPan and UC then their growth kinetics, molecular characterization and mesodermal differentiation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…After 7 days of differentiation in direct cell-cell contact with BM-MSC, under serum-free conditions supplemented with cytokines, 25% of cells were polyploid (DNA content > 4N) when cells were previously expanded for 7 days with the use of the Z9 cocktail. Consistent with this result, Liu et al [24] reported that approximately 25% of Mks (from human UCB), co-cultured with BM-MSC, had higher polyploid content (>4N) after 12 days in culture. UCB-derived Mks generated ex vivo in the present study have shown extended Dm and abundant presence of granules in the cytoplasm.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…After 7 days of differentiation in direct cell-cell contact with BM-MSC, under serum-free conditions supplemented with cytokines, 25% of cells were polyploid (DNA content > 4N) when cells were previously expanded for 7 days with the use of the Z9 cocktail. Consistent with this result, Liu et al [24] reported that approximately 25% of Mks (from human UCB), co-cultured with BM-MSC, had higher polyploid content (>4N) after 12 days in culture. UCB-derived Mks generated ex vivo in the present study have shown extended Dm and abundant presence of granules in the cytoplasm.…”
Section: Discussionsupporting
confidence: 67%
“…It was previously shown that accessory cells such as human MSC from BM, UCB and human BM endothelial cells regulate Mk development and differentiation in vitro [15,45,46]. BM stromal cells provide physical support for HSC/HPC and secret several cytokines/ growth factors such as granulocyte-macrophage colony-stimulating factor, IL-6 and SCF, which act together with TPO to regulate megakaryocytic commitment [15,23,24]. The results of the current study demonstrated that the highest EY (202 AE 34 Mks per seeded CD 34 þ cells) and %CD41 þ content (58% AE 4.9%) in the differentiation stage were achieved by combination of Cyt addition with Feeder co-culture, with the use of a serum-free medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discovery led to the development of a considerable number of coculture systems for the expansion of HSPCs with various sources of feeder cells including BM-derived stromal cells [37,38], immortalized stromal cells [39][40][41] and endothelial cells [42][43][44][45][46] and bone marrow mesenchymal stem cells (MSC) [47][48][49][50][51][52][53]. Examples of such system are presented in Table 1 along with their principal properties and results.…”
Section: Development Of Coculture Procedures and Cytokine Cocktails Fmentioning
confidence: 99%
“…IL-6 also mediates the promotional effect of BM-MSCs and hUC-MSCs in megakaryocytopoiesis [39]. In addition, IL-6 is important in normal wound healing [22] and angiogenesis [21].…”
Section: Cd14mentioning
confidence: 99%